2014
DOI: 10.1039/c4nr00703d
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical interfaces induce high dielectric permittivity in nanocomposites containing TiO2@BaTiO3 nanofibers

Abstract: Interface issues are common and crucial in nanocomposites or nanohybrid systems since the interface area is enormous on the nanoscale. In the 0-3 dimensional polymer nanocomposites, in which nano-inclusions (0-dimension) are embedded in a 3-dimensionally connected polymer matrix, enhanced dielectric permittivity could be induced by the interfacial polarization at the interfaces between the nano-inclusions and the polymer matrix. In this contribution, we propose and demonstrate that the topological structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 30 publications
4
83
0
Order By: Relevance
“…The percolation of the TiO 2 /BaTiO 3 interfaces gives rise to much enhanced interfacial polarization of the BTO@TO_nfs, leading to substantially increased ε r of the polymer nanocomposites (>41) at a rather low volume fraction of ≈10 vol%. [ 18 ] More importantly, improved E B (≈650 kV mm -1 ) is also achieved by taking advantage of the large aspect ratio of the nanofi bers, which is even higher than that of the pristine PVDF matrix. These very favorable features give rise to an ultrahigh energy density of ≈20 J cm -3 .…”
Section: Doi: 101002/adma201404101mentioning
confidence: 99%
See 1 more Smart Citation
“…The percolation of the TiO 2 /BaTiO 3 interfaces gives rise to much enhanced interfacial polarization of the BTO@TO_nfs, leading to substantially increased ε r of the polymer nanocomposites (>41) at a rather low volume fraction of ≈10 vol%. [ 18 ] More importantly, improved E B (≈650 kV mm -1 ) is also achieved by taking advantage of the large aspect ratio of the nanofi bers, which is even higher than that of the pristine PVDF matrix. These very favorable features give rise to an ultrahigh energy density of ≈20 J cm -3 .…”
Section: Doi: 101002/adma201404101mentioning
confidence: 99%
“…An in situ observation of electric breakdown of the TO@BTO_nfs by TEM further confi rms that the electric breakdown characteristics of the BTO@TO_nfs change from being insulating to more conductive behavior with percolating interfacial regions. [ 18 ] Indeed, atomic-scale structural characterization reveals that an interfacial region about 2 nm exists around each BaTiO 3 particle embedded in the TiO 2 nanofi bers. Figure 4 a provides the simulated angular bright-fi eld (ABF) images of BaTiO 3 and TiO 2 , from which we should notice that there is no contrast between two Ba atoms in BaTiO 3 while there always exists a dark contrast between two relative dark contrast in TiO 2 along the horizontal direction.…”
Section: Doi: 101002/adma201404101mentioning
confidence: 99%
“…However, the dielectric permittivities of polymer dielectrics are usually very low (below 10 @1 kHz), which greatly hindered their wide applications. Toward this end, two strategies have been developed to improve the dielectric constants of polymer composites: (1) ceramic-polymer composites composed of high-k ceramic fillers (e.g., BaTiO 3 [23][24][25][26][27], TiO 2 [28,29], SrTiO 3 [30]) dispersed in polymer matrix and (2) conductor-polymer composites consisting of conductors (e.g., metals, [31,32], graphite [33,34], carbon nanotube [35][36][37], graphene [38,39], carbon black [40], and conductive polymer [41,42]) dispersed in polymer matrix. For ceramic-polymer composites, the enhancement of permittivity is limited (below 50 @10 kHz) even when the ceramic loading excesses 50 vol%, leading to deteriorated mechanical properties, high loss, and low breakdown strength [43].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have demonstrated that the morphology and geometry of ceramic nanoparticles influence the dielectric properties of nanocomposites222324. For 0–3 type ceramic-polymer nanocomposites, where spherical zero-dimensional ceramic nanoparticles are embedded in a three-dimensionally connected polymer matrix, a high volume fraction (>50 vol%) of nanoparticles is necessary to achieve a high permittivity nanocomposite.…”
mentioning
confidence: 99%